2021
DOI: 10.1007/s12206-021-1101-3
|View full text |Cite
|
Sign up to set email alerts
|

Review of the binary mixture droplet evaporation studies

Abstract: Understanding the evaporation characteristics of sessile binary mixture droplets (BMDs) is crucial in various industries, such as surface coating, ink-jet printing, evaporators, fuel combustion, and medical diagnosis. The underlying physics of BMDs has not yet been fully explored despite numerous prior studies. This paper reviews the recent studies on evaporating BMD and examines various studied and unaddressed issues. First, we introduce measurement techniques to estimate time-varying mixture concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 83 publications
0
3
0
1
Order By: Relevance
“…Вступ. При випаровуванні крапель бінарного розчину відоме поняття «вибіркового випаровування» [1], при якому більш летючий компонент випаровується швидше, оскільки його тиск насиченої пари біля поверхні краплівищий. В якості бінарних розчинів, як об'єктів таких досліджень, часто використовуються розчини води та спиртів (етанолу, метанолу, бутанолу) [2][3][4][5], різних спиртів (ізопропанолу та бутанолу) [6].…”
Section: теоретичне та експериментальне дослідження тепломасообміну і...unclassified
“…Вступ. При випаровуванні крапель бінарного розчину відоме поняття «вибіркового випаровування» [1], при якому більш летючий компонент випаровується швидше, оскільки його тиск насиченої пари біля поверхні краплівищий. В якості бінарних розчинів, як об'єктів таких досліджень, часто використовуються розчини води та спиртів (етанолу, метанолу, бутанолу) [2][3][4][5], різних спиртів (ізопропанолу та бутанолу) [6].…”
Section: теоретичне та експериментальне дослідження тепломасообміну і...unclassified
“…69 The evaporation behavior of liquid mixtures is also under active exploration because of its practical relevance to real systems and technologies where materials involved are typically multicomponent. [70][71][72][73][74][75] Interestingly, Song et al showed that when the mixture of a volatile (methanol) and a much less volatile (1-butanol) component is evaporated, the two components develop opposite concentration gradients at the evaporation front, with 1-butanol enriched and methanol depleted near the interface. 76 It is interesting to explore if such inhomogeneity in solvent distribution that has developed during evaporation because of the contrasting volatilities of the mixed solvent components can be utilized to tune the distribution of colloidal particles in a drying film.…”
Section: Introductionmentioning
confidence: 99%
“…The evaporation rate for a droplet of a binary solution consisting of two different liquid components is not constant and changes in time, because each component evaporates at a different rate. This phenomenon is called "selective evaporation" [1]: the C i t a t i o n: Kopiyka O.K., Kalinchak V.V., Chernenko A.S. Evaporation of droplets of binary mixtures of lower monohydric alcohols in heated air.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, when determining the concentrations of components during the droplet evaporation, changes in the geometry of a droplet lying on a certain surface were studied [1][2][3]. One of the characteristic parameters is the contact angle, the angle between the droplet-air boundary and the surface, which is governed by the surface tensions at the interfaces between the contacting phases.…”
Section: Introductionmentioning
confidence: 99%